Considering gemcitabine‐based combination chemotherapy as a potential treatment for advanced oesophageal cancer: A meta‐analysis of randomised trials. Issue 7 (29th April 2020) - Yang, Jian; Liang, Xiao; Zhai, Yuanfang; Hu, Xiaoling; Jia, Zhiwu; Cheng, Xiaolong
Abstract: Background: Gemcitabine has been proved to be effective in many advanced cancer. However, almost all trials failed to demonstrate the response rate of gemcitabine‐based combination schedules on oesophageal cancer (EC). Methods: A systematic meta‐analysis of randomised clinical trials (RCTs) was performed to investigate the efficacy of gemcitabine‐based combination chemotherapy in EC treatment. Clinical trials were collected during the period ranging from January 2000 to November 2018 by searching different databases. Odds‐ratios (ORs) of response rate (RR), disease control rate (DCR) and grade 3‐4 toxicity rates (TRs) were extracted as presented in retrieved studies. Results: Fourteen trials (1024 patients) were selected for the final analysis. The results showed that RR and DCR of gemcitabine‐based combination chemotherapy demonstrated a significant advantage for non‐gemcitabine therapy (OR for RR: 1.51; 95% CI: 1.16‐1.96; P  = .002; OR for DCR: 1.66; 95% CI: 1.19‐2.32, P  = .003). Toxicities of gemcitabine‐based combination chemotherapy on gastrointestinal tract (OR, 0.39; 95% CI: 0.24‐0.63, P  = .0001) were less frequent compared to that of the non‐gemcitabine therapy. Conclusion: The improvements of gemcitabine‐based combination chemotherapy on RR, CDR and reduction of gastrointestinal tract, hepatic and renal for EC patients suggests that the combined chemotherapy based on gemcitabine could be a potential treatment options for advanced EC.